Intraneural Ganglion of the Peroneal Nerve-A Rare Cause of Pediatric Peroneal Nerve Palsy: A Case Report - Florian Bucher; Vincent Maerz; Doha Obed; Peter M. Vogt; Birgit Weyand (Georg Thieme Verlag KG, 2022)
Intraneural ganglia are benign mucinous cysts located within the epineurium of a peripheral nerve. The pathogenesis and formation of intraneural ganglia are controversial. The main theories described in the literature are of degenerative, synovial or de novo occurrence. We present the case of a 14-year-old boy who presented in our outpatient clinic with a complaint of interdigital neuralgia between hallux and second toe, as well as left foot drop. MRI examination showed a hyperintense cystic distension of the common peroneal nerve measuring 130 mm × 5 mm extending from the poplitea to the anterior compartment of the leg. We performed microscopic decompression and neurolysis surgery. The cyst showed a sac-like distension at its distal end with connection to the tibiofibular joint and was resected. After 8 weeks, postoperatively, the boy claimed to be pain-free and slight recovery of the superficial peroneal nerve was noticed. At 6 months postoperative, the patient showed a continuous improvement of motor function, demonstrating foot eversion with 3/5 muscle strength and foot extension with 2/5 muscle strength. Intraneural ganglia reported for pediatric patients represent a very rare entity. To the best of our knowledge, less than 15 cases have been described within the English-speaking literature.